Hospitalist-Operated Compression Ultrasonography: a Point-of-Care Ultrasound Study (HOCUS-POCUS) - Fischer, Ernest A.; Kinnear, Benjamin; Sall, Dana; Kelleher, Matthew; Sanchez, Otto; Mathews, Benji; Schnobrich, Daniel; Olson, Andrew P. J. (Journal of general internal medicine : JGIM, 2019)
Background Venous thromboembolism includes deep vein thrombosis (DVT) and pulmonary embolism. Compression ultrasonography is the most common way to evaluate DVT and is typically performed by sonographers and interpreted by radiologists. Yet there is evidence that ultrasound examinations can be safely and accurately performed by clinicians at the bedside. Objective To measure the operating characteristics of hospital medicine providers performing point-of-care ultrasound (POCUS) for evaluation of DVT. Design This is a prospective cohort study enrolling a convenience sample of patients. Hospital medicine providers performed POCUS for DVT and the results were compared with the corresponding formal vascular study (FVS) interpreted by radiologists. Participants Hospitalized non-ICU patients at four tertiary care hospitals for whom a DVT ultrasound was ordered. Main Measures The primary outcomes were the sensitivity, specificity, and predictive values of the POCUS compression ultrasound compared with a FVS. The secondary outcome was the elapsed time between order and the POCUS study compared with the time the FVS was ordered to when the formal radiology report was finalized. Key Results One hundred twenty-five limbs from 73 patients were scanned. The prevalence of DVT was 6.4% (8/125). The sensitivity of POCUS for DVT was 100% (95% CI 74–100%) and specificity was 95.8% (95% CI 91–98%) with a positive predictive value of 61.5% (95% CI 35–84%) and a negative predictive value of 100% (95% CI 98–100%). The median time from order to POCUS completion was 5.8 h versus 11.5 h median time from order until the radiology report was finalized ( p = 0.001). Conclusion Hospital medicine providers can perform compression-only POCUS for DVT on inpatients with accuracy similar to other specialties and settings, with results available sooner than radiology. The observed prevalence of DVT was lower than expected. POCUS may be reliable in excluding DVT but further study is required to determine how to incorporate a positive POCUS DVT result into clinical practice.